Nature’s Paradigms for Designing Architectural Envelopes - Fabrizio Tucci (Agathón)
Nature has perfected strategies and solutions to optimize how resources - material and immaterial resources, physical resources, and energy resources - are transferred, selected, filtered, and metabolically exchanged. Today, at a time of scarce resources, environmental and economic crisis, climate change and constant emergency, researchers have to exploit this potential wealth of knowledge. And it is important to understand the lines of development for research in the future which this paper summarizes in ten men points, referring to dynamic envelopes with variable properties - both opaque / semi-opaque and transparent/translucent.